Synthesis and biological evaluation of benzimidazoles/1, 3, 5-triazine-2, 4-diamine hybrid compounds: a new class of multifunctional alzheimer targeting agents. (27th July 2022) - Karimian, Somaye; Shekouhy, Mohsen; Pirhadi, Somayeh; Iraji, Aida; Attarroshan, Mahshid; Edraki, Najmeh; Khoshneviszadeh, Mehdi
Abstract : Twelve novel benzimidazole/1, 3, 5-triazine-2, 4-diamine hybrids were synthesized and biologically studied as multifunctional Alzheimer-controlling agents. Abstract : In this study, a series of new benzimidazole/1, 3, 5-triazine-2, 4-diamine hybrid derivatives (9a–9l ) were designed and synthesized. The potential multi-target profiles of these compounds to control Alzheimer's disease were then investigated with the in vitro assessment of their AChE, BuChE, and BACE1 and metal chelating activities. The results showed that compounds 9c and 9f are effective inhibitors of all three studied enzymes, AChE (19.01 ± 0.57 μM and 21.09 ± 1.89 μM respectively), BuChE (12.69 ± 1.79 μM and 13.17 ± 0.36 μM, respectively) and BACE1 (32.35 ± 2.38 μM and 49.67 ± 1.43, respectively). On the other hand, compounds 9a and 9b were effective against BuchE (45.17 ± 1.65 μM and 38.21 ± 0.72, respectively) and BACE1 (13.80 ± 2.02 μM and 24.54 ± 1.96 μM, respectively). Besides, compounds 9i and 9l exhibited higher effectiveness against AChE (42.75 ± 0.38 μM and 27.19 ± 1.05 μM, respectively) and BuChE (25.43 ± 1.16 μM and 11.23 ± 2.07 μM, respectively). The molecular modeling studies and molecular dynamics analysis indicated that the synthesized hybrid compounds simultaneously interacted with the catalytically active sites (CAS) and the peripheral anionic sites (PAS) of AChE and BuChE. The kinetic studies of the most potent compounds (9c and 9l ) revealed the mixed type of inhibition on AChE and BuChE with respective K i values of 96.01 μM and 230.4 μM, which confirmed their dual binding nature. In silico analyses of absorption, distribution, metabolism, and excretion (ADME) profiles of the synthesized compounds showed that these molecules followed drug-likeness rules and displayed acceptable predictive ADMET features.